NINJ1 oligomerises on large apoptotic cell-derived extracellular vesicles to regulate vesicle stability and cellular content release - Shi, Bo; Tang, Caolingzhi; Rutter, Stephanie F.; Audi, Omar; Ozkocak, Dilara C.; Trenerry, Alice M.; Simpson, Daniel S.; Williams, Scott A.; Le, Quan T.; Ryan, Gemma F.; Cooray, Ponsuge T. M.; Vince, James E.; et al. (Frontiers in Immunology, 2025)
Billions of cells undergo apoptosis, a non-inflammatory form of programmed cell death, daily as part of normal development and homeostasis. Apoptotic cells undergo apoptotic cell disassembly to release large extracellular vesicles (EVs) called apoptotic bodies (ApoBDs) to promote dead cell clearance, or otherwise proceed to an inflammatory, lytic outcome (i.e., secondary necrosis). The latter event is regulated by ninjurin-1 (NINJ1), a key executioner of plasma membrane rupture (PMR) through its oligomerisation. However, the precise role of NINJ1 at the intersection of apoptotic cell disassembly and secondary necrosis remain elusive. Here, we show that NINJ1 increasingly oligomerises upon the completion of apoptotic cell disassembly process and that higher-order NINJ1 oligomerisation occurs on ApoBDs. We also demonstrate that NINJ1 regulates PMR of ApoBDs and the release of inflammatory signals and, in part, norovirus particles. Together, our findings provide new insights into NINJ1-mediated PMR and content release-associated functions of ApoBDs.